A vanillin‐containing DOPO‐based compound for improving the flame retardancy of epoxy resin simultaneously with comparable transparency and mechanical property. Issue 9 (24th December 2022) - Lu, Jiayi; Chen, Liping; Luo, Zhonglin; Wang, Biaobing
Abstract: A compound containing phosphorus/nitrogen/sulfur (named as DOVNPT) was synthesized by the reaction of p‐toluenesulfonamide, vanillin and 9, 10‐dihydro‐9‐oxo‐10‐phosphophenanthrene‐10‐oxide, and was adopted to prepare flame retardant epoxy resins (FREPs) using 4, 4‐diaminodiphenylmethane as the curing agent. The chemical structure of DOVNPT was verified using Fourier‐transform infrared spectroscopy, 1 H and 31 P nuclear magnetic resonance. The influence of the DOVNPT content on the thermal stability, fire performance, combustion behaviors, transparency and mechanical properties of the FREPs was investigated in detail. The DOVNPT promoted the decomposition of EP on advance whilst lowered the maximum decomposition rate. With the incorporation of 4 wt% DOVNPT (0.49 wt% phosphorus content), the FREP‐4 achieved a LOI value of 34.4% and a UL‐94 V‐0 rating. The FREP‐4 also gave the lowest peak heat release rate, total heat release and total smoke release, with a reduction of 40.4%, 24.8%, and 28.6% as compared with the pure EP, respectively. The comprehensive analysis of the char residues and gaseous pyrolysis products demonstrated that the DOVPNT displayed good flame retardant effect in both gas phase and condensed phase. Simultaneously, the FREPs presented a comparable transparency and slightly improved mechanical properties as compared with the pure EP. Abstract :